Neurodegenerative diseases and catechins: (−)-epigallocatechin-3-gallate is a modulator of chronic neuroinflammation and oxidative stress - Li, Siying; Wang, Zaoyi; Liu, Gang; Chen, Meixia (Frontiers in Nutrition, 2024)
Catechins, a class of phytochemicals found in various fruits and tea leaves, have garnered attention for their diverse health-promoting properties, including their potential in combating neurodegenerative diseases. Among these catechins, (-)-Epigallocatechin-3-gallate (EGCG), the most abundant polyphenol in green tea, has emerged as a promising therapeutic agent due to its potent antioxidant and anti-inflammatory effects. Chronic neuroinflammation and oxidative stress are key pathological mechanisms in neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD). EGCG has neuroprotective efficacy due to scavenging free radicals, reducing oxidative stress and attenuating neuroinflammatory processes. This review discusses the molecular mechanisms of EGCG's anti-oxidative stress and chronic neuroinflammation, emphasizing its effects on autoimmune responses, neuroimmune system interactions, and focusing on the related effects on AD and PD. By elucidating EGCG's mechanisms of action and its impact on neurodegenerative processes, this review underscores the potential of EGCG as a therapeutic intervention for AD, PD, and possibly other neurodegenerative diseases. Overall, EGCG emerges as a promising natural compound for combating chronic neuroinflammation and oxidative stress, offering novel avenues for neuroprotective strategies in the treatment of neurodegenerative disorders.